Removal of Cr (VI) from aqueous solutions by nano-sized magnetite modified with SDS - Ali Akbar Babaei; Zeinab Baboli; Mehdi Ahmadi; Nematollah Jaafarzadeh; Gholamreza Goudarzi; Azar Mostufi (Iranian South Medical Journal, 2015)
Background: Contamination of aquatic bodies with heavy metals is a serious environmental problem. Chromium is a common contaminant in ground and surface water, soil and wastewater. The aim of this study was to use magnetite nanoparticles modified by sodium dodecyl sulphate (SDS) for removal of hexavalent chromium from aqueous solutions and various factors affecting the uptake behavior such as pH, contact time, initial concentration of metal ions, adsorbent concentration, were studied.